An Investigation into Text-Image Coherence in Vocabulary Teaching: A Case Study of the “Text-Image Interactive Units” in the New Grade 7 English Textbook (PEP) - Yu, Huiling; Su, Yujie; Cao, Yangyang; Qiu, Xiaofan; Teng, Hongda (Advances in Social Sciences Research Journal, 2026)
This study explores text-image coherence in the “Text-Image Interactive Units” of the 2024 new Grade 7 English textbook (PEP) using content analysis and case study, based on a four-dimensional framework (temporality, semantics, functionality, multimodality). Results show that text-image coherence in vocabulary teaching presents cross-volume features of word-image synchronization, direct matching and vocabulary recognition assistance, with obvious adaptability differences among parts of speech. Abstract vocabulary has prominent multi-dimensional coherence defects, and insufficient functional support is the core problem. Differentiated design by part of speech and cross-volume gradient adjustment are suggested for optimization. The innovation of this study is to break static text-image analysis, adopt a dynamic perspective of vocabulary teaching, combine multimodal symbol analysis with defect diagnosis, and make up for the limitations of previous static research.